Legal nature and legal Essenes nature of international legal assistance in civil matters - Ємець, І. О. (Problems of legality, 2015)
The article deals with the question of the legal nature and essence of international legal assistance in civil matters, and, by the way, with the content of international legal obligations of States in the given area and implementations of that obligations. Special attention is paid to the concept of international legal assistance, as defined in the relevant of international treaties and international public law mechanisms by which ensured the implementation of such agreements.